Andean Forests of Southern Ecuador, classification, regeneration and use - Bussmann, Rainer W. (2005)
Few floristic inventories and even less syntaxonomical vegetation descriptions of tropical mountain forests exist. The author presents a syntaxonomical treatment of the vegetation of Reserva Biológica of San Francisco at the northern limit of Podocarpus National Park, Ecuador, together with notes on the corresponding soil types. The Lower Montane Forest (1800-2150 m), grouped in the new order Alzateetalia verticillatae, has a very diverse tree layer 20-35 m tall, and are a typical mosaic-climax. It grows on Terric Haplosaprists and Aquic Dystrupepts, developed from old landslide material and extends up to elevations of 2300 m at the bottom of wind-protected riverine valleys. At altitudes from 2100-2650 m (–2750 m), the forest structure and floristic composition change completely. The vegetation types belonging to this Upper Montane Forest form the newly described Purdiaeaetalia nutantis, growing on Histic Petraquepts. They represent a monotypic vegetation, with only one tree stratum, and stems between 5-10 m, rarely up to 15 m tall. The canopy is completely dominated by the twisted stems of Purdiaea nutans (Cyrillaceae). The Subalpine-elfin forest which closely resembles that of the the Bolivian Jalca forms the uppermost forest belt of the study area. Described as Clusio ellipticae-Weinmannietum cochensis, this forest —more like an impenetrable bushland— grows on Humaqueptic Epiaquents and is closely dovetailed with the adjacent páramo region. The timberline in the area is mainly induced by strong winds. Charcoal was found at the base of the A horizons of many soil profiles up to the top region and 14C dated to 710-980 +/-50 years BP. This indicates that vegetation fires occurred in the past, and are not only a recent phenomenon.